Noninvasive in vivo Assessment of the Re‐endothelialization Process Using Ultrasound Biomicroscopy in the Rat Carotid Artery Balloon Injury Model. (13th November 2018) - Röhl, Samuel; Eriksson, Linnea; Saxelin, Robert; Lengquist, Mariette; Östenson, Claes‐Göran; Hedin, Ulf; Caidahl, Kenneth; Razuvaev, Anton
Abstract : Objectives: Ultrasound biomicroscopy (UBM), or ultra high‐frequency ultrasound, is a technique used to assess the anatomy of small research animals. In this study, UBM was used to assess differences in intimal hyperplasia thickness as a surrogate measurement of the re‐endothelialization process after carotid artery balloon injury in rats. Methods: Ultrasound biomicroscopic data from 3 different experiments and rat strains (Sprague Dawley, Wistar, and diabetic Goto‐Kakizaki) were analyzed. All animals were subjected to carotid artery balloon injury and examined with UBM (30–70 MHz) 2 and 4 weeks after injury. Re‐endothelialization on UBM was defined as the length from the carotid bifurcation to the most distal visible edge of the intimal hyperplasia. En face staining with Evans blue dye was performed at euthanasia 4 weeks after injury, followed by tissue harvesting for histochemical and immunohistochemical evaluations. Results: A significant correlation (Spearman r = 0.63; P < .0001) was identified when comparing all measurements of re‐endothelialization obtained from UBM and en face staining. The findings revealed a similar pattern for all rat strains: Sprague Dawley (Spearman r = 0.70; P < .0001), Wistar (Spearman r = 0.36; P < .081), and Goto‐Kakizaki (Spearman r = 0.70; P < .05). A Bland‐Altman test showed agreement between en face staining and UBM. Immunohistochemical staining confirmed the presence of the endothelium in the areas detected as re‐endothelialized by the UBM assessment. Conclusions: Ultrasound biomicroscopy can be used for repeated in vivo assessment of re‐endothelialization after carotid artery balloon injury in rats.